On the Optimality of the Multi-Product EOQ Model with Pricing Consideration - Shin, Ho-Jung; Park, Soo-Hoon (Management science & financial engineering, 2012)
Two previous studies that attempted to generalize the deterministic joint pricing-inventory decision model are re-evaluated. We prove analytically that even in a single-product environment, the EOQ model with constant price-elastic demand cannot find optimal solutions unless two optimality conditions associated with price elasticity and demand magnitude are satisfied. Due to the inexistence of the general optimality for the problem, demand function and price elasticity must be evaluated and bounded properly to use the methods proposed in the previous studies. KCI Citation Count: 1